Latent structure of the proposed ICD-11 post-traumatic stress disorder symptoms: Implications for the diagnostic algorithm. (March 2015) - Forbes, David; Lockwood, Emma; Creamer, Mark; Bryant, Richard A.; McFarlane, Alexander C.; Silove, Derrick; Nickerson, Angela; O'Donnell, Meaghan
Abstract : Background: The latent structure of the proposed ICD-11 post-traumatic stress disorder (PTSD) symptoms has not been explored. Aims: To investigate the latent structure of the proposed ICD-11 PTSD symptoms. Method: Confirmatory factor analyses using data from structured clinical interviews administered to injury patients ( n = 613) 6 years post-trauma. Measures of disability and psychological quality of life (QoL) were also administered. Results: Although the three-factor model implied by the ICD-11 diagnostic criteria fit the data well, a two-factor model provided equivalent, if not superior, fit. Whereas diagnostic criteria based on this two-factor model resulted in an increase in PTSD point prevalence (5.1% v. 3.4%; z = 2.32, P <0.05), they identified individuals with similar levels of disability ( P = 0.933) and QoL ( P = 0.591) to those identified by the ICD-11 criteria. Conclusions: Consistent with theorised reciprocal relationships between re-experiencing and avoidance in PTSD, these findings support an alternative diagnostic algorithm requiring at least two of any of the four re-experiencing/avoidance symptoms and at least one of the two hyperarousal symptoms.